The COVID-19 Symptom to Isolation Cascade in a Latinx Community: A Call to Action. (20th January 2021) - Rubio, Luis A; Peng, James; Rojas, Susy; Rojas, Susana; Crawford, Emily; Black, Douglas; Jacobo, Jon; Tulier-Laiwa, Valerie; Hoover, Christopher M; Martinez, Jackie; Jones, Diane; Sachdev, Darpun; et al.
Abstract: Background: Rapid coronavirus disease 2019 (COVID-19) diagnosis and isolation of infectious persons are critical to stopping forward transmission, and the care cascade framework can identify gaps in the COVID-19 response. Methods: We described a COVID-19 symptom to isolation cascade and barriers among symptomatic persons who tested polymerase chain reaction positive for severe acute respiratory disease coronavirus 2 (SARS-CoV-2) at a low-barrier testing site serving a low-income Latinx community in San Francisco. Steps in the cascade are defined as days from symptom onset to test, test to result, and result to counseling on self-isolation. We examined SARS-CoV-2 cycle threshold (Ct) values to assess the likelihood of infectiousness on the day of testing and during missed isolation days. Results: Among 145 persons, 97% were Latinx and 81% had an income of <50 000. The median time from symptom onset to isolation (interquartile range [IQR]) was 7 (5–10) days, leaving a median (IQR) of 3 (0–6) days of isolation. Eighty-three percent had moderate to high levels of virus (Ct <33), but by disclosure 23% were out of their isolation period. The longest intervals were symptom onset to test (median [IQR], 4 [2–9] days) and test to results notification (median [IQR], 3 [2–4] days). Access to a test site was the most common barrier to testing, and food and income loss was the most common barrier to isolation. Conclusions: Over half of the 10-day isolation period passed by the time of disclosure, and over a fifth of people were likely outside the window of infectiousness by the time they received results. Improvements in test access and turnaround time, plus support for isolation, are needed for epidemic control of SARS-CoV-2 in highly impacted communities.